Upacara Seren Taun di Cigugur, Kabupaten Kuningan, Jawa Barat: Tradisi Sebagai Basis Pelestarian Lingkungan - Royyani, Mohammad Fathi (Perhimpunan Biologi Indonesia, 2008)
ABSTRACTSeren Taun Ceremony at Cigugur, Kuningan District, West Jawa: TraditionalCeremonial For Environment Conservation. Human being couldnât be separatedfrom the environment, but in reality the damage of the land is precisely caused by humanbehavior. The reason of this is that people donât have good relationship with the surroundingenvironment. Following this logic, with participatory observation I have done it in February4 until 15th, 2004, the indigenous people with their tradition have their own way toconserve the land. They have a ritual tradition that can be used as a means of educationfor their adherent. Furthermore, ritual traditions also show the nearness of emotionalrelationship between human and the environment.Keywords: environtment, ritual tradition, Cigugur Kuningan